Contactless and Rapid Discrimination of Improvised Explosives Realized by Mn2+ Doping Tailored ZnS Nanocrystals. (2nd May 2016) - Wu, Zhaofeng; Zhou, Chaoyu; Zu, Baiyi; Li, Yushu; Dou, Xincun
Abstract : In order to sensitively, selectively, and rapidly detect the constituents relevant to improvised explosive devices (IEDs), the sensing properties of ZnS nanocrystals (NCs) are regulated by tailoring the doping level of Mn 2+ . The responses of the sensors fabricated by ZnS NCs with different Mn‐doping levels (Mn:ZnS) toward the constituents, such as sulphur powder and black powder, generally increases first and then decreases with the increase of the concentration of doped Mn 2+, and reaches the climate with an atomic ratio of 2.23% at room temperature. The sensory array based on eight sensors of Mn:ZnS NCs can realize the detection of two typical military explosives and six constituents relevant to IEDs within 7 s and can recover in 19 s. Furthermore, the fingerprinting of the constituents is achieved by pattern recognizing the inherent kinetics and thermodynamics of interaction between the sensory array and the constituents. Thus, a simple chemiresistive sensing strategy based on semiconductor NCs which can rapidly, supersensitively, and discriminatively detect the constituents relevant to IEDs is explored for the first time. Abstract : A chemiresistive sensing scheme to sensitively and rapidly detect the vapors of the constituents relevant to improvised explosive devices (IEDs) at room temperature is achieved by tailoring the sensing properties of ZnS nanocrystals. The resulting differential identification capability toward explosives makes the on‐the‐spot detection of IEDs possible.